2019
DOI: 10.2147/ott.s217347
|View full text |Cite
|
Sign up to set email alerts
|

<p>Key Genes And Pathways Controlled By E2F1 In Human Castration-Resistant Prostate Cancer Cells</p>

Abstract: Point your SmartPhone at the code above. If you have a QR code reader the video abstract will appear. Or use: https://www.youtube.com/watch?v=vyHEYxL16_M Background: Treatment of castration-resistant prostate cancer (CRPC) is an enormous challenge. As E2F transcription factor 1 (E2F1) is an essential factor in CRPC, this study investigated the genes and pathways controlled by E2F1 and their effects on cellular behavior in CRPC. Methods: In vitro assays were used to evaluate cellular proliferation, apoptosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Similarly, knockout of CREB in PC3 cells resulted in reduced xenograft tumorigenicity in nude mice. We and others have previously demonstrated that TFDP3 is highly expressed in prostate cancer tissues, and not expressed or lowly expressed in normal tissues (2). TFDP3 inhibits the DNA binding, E2F1 transactivation and E2F1-dependent apoptosis (2,6).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Similarly, knockout of CREB in PC3 cells resulted in reduced xenograft tumorigenicity in nude mice. We and others have previously demonstrated that TFDP3 is highly expressed in prostate cancer tissues, and not expressed or lowly expressed in normal tissues (2). TFDP3 inhibits the DNA binding, E2F1 transactivation and E2F1-dependent apoptosis (2,6).…”
Section: Discussionmentioning
confidence: 85%
“…E2F1 can regulate a large number of genes involved in diverse cellular processes, such as replication, apoptosis, checkpoint control, and DNA repair (21). We previously demonstrated that E2F1 could regulate the expression of TFDP3, while TFDP3 could negatively regulate E2F1 by inhibiting DNA binding and E2F1 transactivation (2). Hence, the binding of CREB/TFDP3 and upregulation of CREB may inhibit E2F1-dependent apoptosis by enhancing the activity of TFDP3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations